Bio-medical waste management in different hospitals of Guwahati and its effect on environment - Changmai, Arabinda; Islam, Tofiqul; Nongsiang, Dibarlan; Deka, Manoj Kumar; Saharia, Bhargab Jyoti; Choudhury, Ananta; Dey, Biplab Kumar (Journal of Applied Pharmaceutical Research, 2018)
Biomedical waste is defined as the waste generated during the diagnosis, treatment or immunization of human beings or animals or in research activities pertaining thereto or in the production or testing of biological, and including categories mentioned in schedule I of the Biomedical Waste (Management and handling) (second amendment) Rules 2000, by Ministry of Environment and Forests notification. Proper handling, treatment and disposal of biomedical wastes are important elements of healthcare infection control program. There may be increased risk of nosocomial infections in patients due to poor waste management which can lead to change in microbial ecology and spread of antibiotic resistance. It is not only the health of the patient, but also the health of persons in health care industry equally important. This article speaks about how the hospitals present in Guwahati treat their waste material and the effect of the waste in the environment Keywords: Biomedical waste, waste management, effect on environment, risk associate.